2013
DOI: 10.1089/end.2012.0381
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Small Renal Masses: Practice Patterns at Academic Institutions in the United States

Abstract: Ablative technologies are well utilized for the treatment of small renal masses at current academic institutions with urologists directly involved in the ablation procedure in only half of the institutions. While preablation biopsy is common, pathology is rarely known prior to ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 18 publications
0
12
0
2
Order By: Relevance
“…2,5,6,13,23,24 A recent survey of practice patterns at academic centers in the United States report performing a biopsy of a renal mass using CB (67%), FNA (5%), and CB and FNA (28%). 25 Most reviews and series suggest that FNA and CB are complementary procedures, and a combined approach will increase diagnostic utility due to the differing advantages and disadvantages of each modality. 1,4,22,26 The advantages of FNA are more extensive sampling of the entire lesion and rapid on-site evaluation, and the disadvantages are less specific information on tumor type and grade.…”
Section: Diagnostic Utility Of Fnamentioning
confidence: 99%
“…2,5,6,13,23,24 A recent survey of practice patterns at academic centers in the United States report performing a biopsy of a renal mass using CB (67%), FNA (5%), and CB and FNA (28%). 25 Most reviews and series suggest that FNA and CB are complementary procedures, and a combined approach will increase diagnostic utility due to the differing advantages and disadvantages of each modality. 1,4,22,26 The advantages of FNA are more extensive sampling of the entire lesion and rapid on-site evaluation, and the disadvantages are less specific information on tumor type and grade.…”
Section: Diagnostic Utility Of Fnamentioning
confidence: 99%
“…In a survey of 64 institutions performing ablative procedures for SRMs, Patel et al identified laparoscopic CA as the most commonly performed ablative procedure [5].…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In the most recent survey of American academic centres, Patel et al found that LTA was available at all academic centres (compared to 85.1% of academic centres in our study). 8 They also reported that most centres had access to laparoscopic cryoablation (83%) or laparoscopic radiofrequency (20%). This contrasts with low access rates to laparoscopic cryoablation (9%) or radiofrequency (7%) in Canada.…”
Section: Discussionmentioning
confidence: 47%
“…The main one resides in the low response rate (19.5%). This response is lower than the one reported by Bandi et al (62%) 9 and the one reported by Patel et al (52%) 8 in similar surveys from the U.S. However, in those cases, the survey was sent directly to all academic centres, thus not comprising other types of practices.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation